2007
DOI: 10.1007/s00192-007-0470-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of retention of urine after caesarean section

Abstract: Caesarean section poses higher risk of postpartum urinary retention (PUR) than vaginal delivery. The aim of this study was to identify the prevalence and the associated risk factors of PUR after caesarean section. Two hundred seven parturients (mean age = 31.26 years old, median parity = 0) who delivered by caesarean section were recruited from the postnatal unit of a tertiary hospital in Hong Kong. Voiding was encouraged 6 h after removal of Foley catheters. Transvaginal ultrasound scan was performed immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 35 publications
0
28
0
1
Order By: Relevance
“…Postoperative urinary disturbance after cesarean section is also a relatively common occurrence, which may be affected by various factors such as postpartum bladder dysfunction and complications by surgical or anesthetic procedures [1][2][3]. It is reported that 1) multiple pregnancy, 2) lack of progress in labor, 3) low maternal body mass index and 4) use of postoperative analgesia are the risk factors for postpartum urinary retention after cesarean delivery [2,4,5]. Therefore, this case was thought to be high risk for postpartum urinary retention because it meets the factors (3) and (4) described above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative urinary disturbance after cesarean section is also a relatively common occurrence, which may be affected by various factors such as postpartum bladder dysfunction and complications by surgical or anesthetic procedures [1][2][3]. It is reported that 1) multiple pregnancy, 2) lack of progress in labor, 3) low maternal body mass index and 4) use of postoperative analgesia are the risk factors for postpartum urinary retention after cesarean delivery [2,4,5]. Therefore, this case was thought to be high risk for postpartum urinary retention because it meets the factors (3) and (4) described above.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this case was thought to be high risk for postpartum urinary retention because it meets the factors (3) and (4) described above. The incidence of postpartum urinary retention associated with postoperative analgesia was reported to be affected by the analgesics and administration methods [4,6]. Epidural analgesia with morphine was thought to increase post-cesarean urinary retention [6].…”
Section: Discussionmentioning
confidence: 99%
“…Chai et al [35] recently noted that cesarean section poses a higher risk of postpartum urinary retention, defi ned in their series as a PVR (by ultrasound) more than 150 mL after removal of the Foley catheter. Logistic regression analysis indicated that the only signifi cant associated factor was "lack of progress in labor."…”
Section: Cesarean Sectionmentioning
confidence: 98%
“…In the literature, most data about postpartum urinary retention focus on vaginal delivery while the exact role of the CS in this complication is still unknown (7). But the clinical risk factors related to POUR must be identified in order to take necessary cautions against poor outcomes of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the reported incidence rate for postcesarean urinary retention varies widely, between 5% and 33.3%, which, in fact, reflects its multifactorial etiology (including comorbidities, type of surgery, and type of anesthesia etc.) and that it lacks a uniform definition (7,10).…”
Section: Introductionmentioning
confidence: 99%